An Anatomy of Corporate Bond Markets : Growing Pains and Knowledge Gains - Luengnaruemitchai, Pipat (IMF Working Papers; Working Paper ;, 2005)
The objective of this paper is to discuss the key issues relating to the development of local corporate bond markets. We examine the requirements for local corporate bond market development, and compare and contrast experiences across both mature and emerging markets. We suggest that core aspects such as benchmarking, corporate governance and disclosure, credit risk pricing, the availability of reliable trading systems, and the development of hedging instruments are fundamental for improving the breadth and depth of corporate debt markets. The demand and supply of corporate bonds are dependent on factors such as the investor base, both local and foreign, and government policies toward the issuance process and associated costs, as well as the taxation regime. The sequencing of reforms is key to market development.